2020
DOI: 10.3390/ijms21041455
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Transcriptomic Regulations behind Metabolic Syndrome in Obese and Lean Subjects

Abstract: Multiple mechanisms have been suggested to confer to the pathophysiology of metabolic syndrome (MetS), however despite great interest from the scientific community, the exact contribution of each of MetS risk factors still remains unclear. The present study aimed to investigate molecular signatures in peripheral blood of individuals affected by MetS and different degrees of obesity. Metabolic health of 1204 individuals from 1000PLUS cohort was assessed, and 32 subjects were recruited to four study groups: MetS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
1
11
1
Order By: Relevance
“…In future studies it would of interest to perform more global approaches to obtain further insights of the usefulness of PBMC to understand the impact of increased adiposity on metabolism and health. For example, the relevance of transcriptome next generation sequencing applied to whole blood for the study of overweight/obesity and metabolic syndrome has been already established 43 . Moreover, lipidomics has been shown to detect changes in plasma lipidome with obesity and metabolic risk 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…In future studies it would of interest to perform more global approaches to obtain further insights of the usefulness of PBMC to understand the impact of increased adiposity on metabolism and health. For example, the relevance of transcriptome next generation sequencing applied to whole blood for the study of overweight/obesity and metabolic syndrome has been already established 43 . Moreover, lipidomics has been shown to detect changes in plasma lipidome with obesity and metabolic risk 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that similar pathways were enriched in our recent transcriptomic study of different metabolic health phenotypes[ 35 ]. The IPA core analysis of differentially expressed genes between MHO and MHNW subjects revealed significant enrichment in EIF2 signaling, regulation of eIF4 and p70S6K signaling, oxidative phosphorylation, mitochondrial dysfunction, and mTOR signaling canonical pathways.…”
Section: Transcriptomicsmentioning
confidence: 95%
“…[ 141 ] Finally, transcriptomics has also reflected the chronic inflammatory state present within the MetS with upregulation of inflammatory genes in MUO patients while MHO patients displayed upregulation of genes involved in oxidative phosphorylation and protein synthesis. [ 142 ] The potential to use these more advanced technologies combined with advances in machine learning will no doubt lead to a greater understanding of obesity sub‐types, their specific risk clusters, and indeed better biomarkers of low‐grade metabolic inflammation.…”
Section: How Do We Measure Metabolic Inflammation?mentioning
confidence: 99%